The worldmakers - Ramachandran, Ayesha (The University of Chicago Press, 2015)
Introduction : worldmaking and the project of modernity – Mapping the body, mapping the world : Mercator's Atlas – On cosmographic autobiography : Montaigne's Essais – Cosmic politics : the worldly epics of Camões and Spenser – Cartesian romance : universal origins and Le monde –
Includes bibliographical references and index
Keywords: Geographical perception; Human geography; Historical geography; Cosmography; Philosophy and science